FORMATION OF STUDENTS' READINESS FOR SELF-EDUCATION AS A CURRENT PEDAGOGICAL PROBLEM (Pedagogy of Higher and Secondary Education, 2010)
This article deals with one of the most important problems in the sphere of education now - the problem of formation of readiness of students to the self-education.
Keywords: self-education; readiness; readiness to the self-education